Questioning the assumptions underpinning modern society in a search for new patterns of governance: government, civil society and companies sailing in a sea of complexity - García Magariño, Sergio (Cuadernos de Gobierno y Administración Pública, 2016)
This paper has three main aims. First, to make an introduction about the concept of governance in order to generate a common language from which to approach, in collaboration with other authors, its manifold facets. Second, to propose a framework with certain questions that, on the one hand, enable different kind of actors to reflect on this important topic – governance – and, on the other, allow for integrating the knowledge generated in this field into a coherent body. Finally, the paper attempts to respond to some of the questions posed at the beginning by looking at the practical implications on the governance mechanisms of certain principles. In this last respect, the underlying assumption is that there must be a dialogue between science and religion to find more effective models of social organization and development. The paper is grounded on the opening remark that the Office or Public Affairs of the Baha’i community of Spain presented in the conference «The paramount need for cooperation: the government, the civil society and the private sector navigating on a sea of complexity» held in the Centro de Estudios Políticos y Constitucionales of Madrid the 22th of May of 2014. The article is divided into four sections: 1. What is meant by governance? 2. The purpose of the conference. 3. Sectors and levels of governance. 4. Calling into question some underlying tenets.